(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Ilurbeda is a deity worshipped in the Roman age mainly in the northeast of the province of Lusitania. The researchers interested in the determination of this deity’s functions and characteristics sometimes overlook an altar from Sintra, Portugal, due to the strong erosion of the inscription and the geographical distance from the remaining inscriptions mentioning this theonym. The present study reassesses the altar from Sintra and presents a full reading of the epigraph and proposes to consider the nature of the divinity and the family revealed in this new reading.